The awareness of Privacy issues in Ambient Intelligence - Mar LÓPEZ (Advances in Distributed Computing and Artificial Intelligence Journal, 2015)
Ambient Intelligence (AmI) involves extensive and invisible integration of computer technologies in people´s daily lives: Smart Sensors, Smart Phones, Tablets, Wireless Sensor Network (Wi-Fi, Bluetooth, NFC, RFID, etc.), Internet (Facebook, WhatsApp, Twitter, You Tube, Blogs, Cloud Computing, etc.). The Intelligent Environments (IE) collect and process a massive amount of person-related and sensitive information. The aim of this work is to show the awareness of privacy issues in AmI and to identify the relevant design issues that should be addressed in order to provide privacy in the design of Ambient Intelligence’s applications focused in the user´s domain and involved technologies. We propose a conceptual framework in order to enforce privacy that takes care of interaction between technologies and devices, users and application´s domain with different modules that contain different steps relating to the privacy policies.